1995
DOI: 10.1111/j.1432-1033.1995.tb20728.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Catalytic Role of Tyrosine 383 in the Peptidase Reaction of Leukotriene A4 Hydrolase

Abstract: Leukotriene A, (LTAJ hydrolase is a bifunctional zinc metalloenzyme which catalyzes the final step in the biosynthesis of the proinflammatory leukotriene B, and which also possesses a peptidase activity. From sequence comparisons with aminopeptidases, a tyrosine at position 383 in LTA, hydrolase has been suggested as a possible catalytic amino acid. To explore the potential role of this amino acid in catalysis, we replaced the tyrosine residue with phenylalanine, histidine or glutamine residues by site-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…Thus, mutagenetic replacements of Glu-296 in LTA 4 hydrolase, a conserved residue within the zinc signature, abrogated only the peptidase activity and not the ability to catalyze the conversion of LTA 4 into LTB 4 , which suggests a direct catalytic role for Glu-296 in the peptidase reaction, possibly as a general base [76,77]. Furthermore, sequence comparisons and mutational analysis have demonstrated that Tyr-383 plays an important role in the peptidase reaction of LTA 4 hydrolase, presumably as a proton donor [78]. Further investigation of the catalytic properties of mutants in position 383 revealed the formation of large quantities of a novel metabolite of LTA 4 structurally identified as 5S,6S-dihydroxy-7,9-trans-11,14-cis-eicosatetraenoic acid (5S,6S-DHETE), in addition to the expected LTB 4 [79].…”
Section: Identification Of Catalytically Important Amino Acid Residuementioning
confidence: 99%
“…Thus, mutagenetic replacements of Glu-296 in LTA 4 hydrolase, a conserved residue within the zinc signature, abrogated only the peptidase activity and not the ability to catalyze the conversion of LTA 4 into LTB 4 , which suggests a direct catalytic role for Glu-296 in the peptidase reaction, possibly as a general base [76,77]. Furthermore, sequence comparisons and mutational analysis have demonstrated that Tyr-383 plays an important role in the peptidase reaction of LTA 4 hydrolase, presumably as a proton donor [78]. Further investigation of the catalytic properties of mutants in position 383 revealed the formation of large quantities of a novel metabolite of LTA 4 structurally identified as 5S,6S-dihydroxy-7,9-trans-11,14-cis-eicosatetraenoic acid (5S,6S-DHETE), in addition to the expected LTB 4 [79].…”
Section: Identification Of Catalytically Important Amino Acid Residuementioning
confidence: 99%
“…Three amino acids (His295, His299 and Glu318) form the Znbinding cluster and mutagenesis studies indicated that the loss of one of these residues blocks the catalytic activity [323][324][325][326]. LTA4H undergoes suicidal inactivation during LTA4 hydrolysis and as molecular reason for the loss in catalytic activity chemical modification of Tyr378 was suggested [327,328]. Additional mechanistic studies indicated the importance of the following amino acids for the functionality of the enzyme: Gln136, Glu271, Glu296, Asp375, Arg563, and Lys565 [6,[329][330][331].…”
Section: Leukotriene A4 Hydrolase (Lta4h)mentioning
confidence: 99%
“…Human recombinant LTA4H was expressed in Escherichia coli and purified to near homogeneity, as previously described (13,30). Greater purity (>95%) was achieved by chromatography on hydroxyapatite (TSKgel HA-1000, Tosoh Biosep GmbH, Stuttgart, Germany) and anion-exchange (Mono-Q HR5/5) resins.…”
Section: Protein Purification and Crystallizationsmentioning
confidence: 99%